Changes in consumption inequality in China - Jing Liu; Shi Li (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2011)
Removed Chapter from: 'Rising Inequality in China: Challenge to a Harmonious Society', edited by Shi Li, Hiroshi Sato and Terry Sicular.
Keywords: 330; Konsum; Soziale Ungleichheit; China